A Geomechanical Approach to Landslide Hazard Assessment: The Multiscalar Method for Landslide Mitigation. (2016) - Cotecchia, Federica; Santaloia, Francesca; Lollino, Piernicola; Vitone, Claudia; Cafaro, Francesco; Bottiglieri, Osvaldo
Abstract: The landslide hazard assessment, when based on the deterministic diagnosis of the processes, can be pursued only through the interpretation and the geo-hydro-mechanical modelling of the slope equilibrium. In practice, though, landslide hazard assessment is still seldom dealt with slope modelling, in particular when it addresses vast areas, where either heuristic or statistical methods do not entail any geo-hydro-mechanical knowledge of slope features and stability. The Multiscalar Method for Landslide Mitigation (MMLM) is an original methodological approach for intermediate to regional landslide hazard assessment. It is based on the geo-hydro-mechanical knowledge achieved from the application of a stage-wise diagnostic methodology of the landslide mechanism at the slope scale. The paper discusses the main steps of the MMLM aiming at diagnoses of landslide hazard based on hydro-mechanics, for small scale hazard mapping (at the large area).